Rapport (International Organisation for Migration Port-au-PrinceHT, 2008)
Bearing in mind that migration management issues have particular relevance to regional security and stability the Consultaation offers a framework to participating immigration services to address common challenges and areas of shared interest. Establishes a mechanism that facilitates cross-border cooperation and coordination on migration and border security matters between the participating countries.
Keywords: MIGRATION